2015
DOI: 10.1007/978-3-319-22723-8_21
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Representation Alternatives for Communicating Uncertainty to Non-experts

Abstract: Abstract. Non-experts are confronted with uncertainty of predictions everyday when, e.g., using a navigation device or looking at the weather forecast. However, there are no standards for representing uncertain information and representations could be easily misleading. Thus, we selected twelve representations that provide different levels of uncertainty information. We compared the representations in an online survey with 90 participants where we asked participants to judge their support in decision-making, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…They suggest displaying a normal probability distribution function and a cumulative probability function on top of each other. This is in line with findings of Greis et al [7], who found that laymen performed best in a game when supported by a probability distribution function plot. Color gradients also proved suitable for visualizing probability distributions [9], and have even been suggested as an alternative to bar charts with error bars [3].…”
Section: Visualization Of Uncertaintysupporting
confidence: 93%
“…They suggest displaying a normal probability distribution function and a cumulative probability function on top of each other. This is in line with findings of Greis et al [7], who found that laymen performed best in a game when supported by a probability distribution function plot. Color gradients also proved suitable for visualizing probability distributions [9], and have even been suggested as an alternative to bar charts with error bars [3].…”
Section: Visualization Of Uncertaintysupporting
confidence: 93%
“…If a statistically significant relationship (p = <0.05) was found, we then used the Wilcoxon signed-rank test as a post hoc analysis to see which two poster responses, and in which criterion, were significantly different. Similar statistical approaches have been used in comparable analyses to this one (Greis et al, 2015;McMahon et al, 2016;Skau et al, 2015).…”
Section: Qualitative Quantitative and Statistical Analysismentioning
confidence: 99%
“…Such visualizations of uncertainty, risk, and probability that are consumed by the public are notoriously difficult to both render and interpret [19,25]. However, uncertainty in visualizations can help people to make better estimates [18], suggesting that uncertainty should be made more obvious in hurricane risk images.…”
Section: Design Implicationsmentioning
confidence: 99%
“…Findings contribute to multiple concerns in the expanding field of human-computer interaction, including that of information visualization and challenges with representing concepts like uncertainty, risk, and probability in consumable ways for a broad public [19,25]; the relationship between formal and informal risk communication by computer-mediated means in disaster response [20,44]; understanding the nature of information diffusion on widely adopted social platforms, and devising methods for that study [17,48]; and supporting needs of the weather scientific and practitioner communities to understand socio-behavioral phenomena around their information products [42].…”
Section: Introductionmentioning
confidence: 98%